Urban-rural disparities in cervical cancer screening among Indian women between 30–49 years: a geospatial and decomposition analysis using a nationally representative survey - Priyanka Garg; Yuvaraj Krishnamoorthy; Pritam Halder; Sathish Rajaa; Madhur Verma; Ankita Kankaria; Anil Goel; Rakesh Kakkar (BMC Cancer)
Abstract Introduction Existing evidence suggests a lower uptake of cervical cancer screening among Indian women. Coverage is lower in rural than urban women, but such disparities are less explored. So, the present study was conducted to explore the self-reported coverage of cervical cancer screening in urban and rural areas stratified by socio-demographic characteristics, determine the spatial patterns and identify any regional variations, ascertain the factors contributing to urban-rural disparities and those influencing the likelihood of screening among women aged 30–49 years factors residing in urban, rural, and overall Indian settings. Methods We did a secondary analysis of the fifth round of the National Family Health Survey in India (2019-21) data with a sample size of 3,48,882 women. The coverage of cervical cancer screening was estimated using sampling weights. Urban-rural differences were compared using the chi-square test. Spatial patterns were analysed using aggregated district-level data, and the contribution of different independent variables to the urban-rural disparities was estimated using multivariate decomposition analysis. Multivariable logistic regression was conducted using STATA 17 to obtain the significant factors of reported screening in urban and rural areas. Results The nationwide coverage of cervical cancer screening was 2.0% (95% CI: 1.9-2.0). The urban (2.4%; 2.3–2.5) participants had higher screening coverage than their rural (1.8%; 1.7–1.8) counterparts. Moran’s I statistic confirmed the presence of spatial dependence and geographical gradient. Decomposition analysis depicted small urban-rural differences in the screening coverage of 0.60% (0.4–0.8). Endowment and coefficient contributed to 88.15% and 11.85% of the disparities. Compositional changes were contributed majorly by regional differences, low education, scheduled tribes, and having living children > 2. Higher odds of having screening were associated with older age (AOR 1.45, 95% CI: 1.03–1.28), higher education (1.32; 1.13–1.55), higher age of first intercourse (1.60; 1.43–1.79), married (1.25; 1.08–1.45) and diabetic (1.39; 1.17–1.65) women, and those from South India (6.76; 5.90–7.75). The odds were lower among Muslims, scheduled tribes and participants using hormonal contraceptives. Conclusion There are significant urban-rural disparities in cervical cancer screening uptake that can be attributed to regional variation, educational inequalities, tribal groups, socio-economic inequalities and parity, necessitating the need to comprehensively design tailor-made advocacy initiatives and simultaneously address the broader determinants of health.